Pengaplikasian Standar ISO 9126 dalam Rancang Bangun Sistem Informasi Inventori dan Pengawasan Laboratorium Berbasis Android - Ari Amir Alkodri; Burham Isnanto Farid; Agus Dendi Rachmatsyah; Ferry Bakti Atmaja (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2023)
Application of ISO 9126 Standard in Designing Android-based Inventory and Laboratory Monitoring Information System - The device inventory process is a recording strategy, grouping devices based on the expiration date, laboratory, condition and others to facilitate the use and data collection of devices in the laboratory. The inventory process makes it easier for equipment data collection staff to monitor and document equipment coming in and out of laboratories where practicum equipment is relatively expensive. Schematic development is a collection of elements that are interconnected with one another to form a single unit to achieve one goal. This research will design an Android laboratory application using an inventory information system and CCTV surveillance. The process of testing applications using ISO 9126 with stakeholders and testing effectiveness, efficiency, and usefulness to ensure applications can be used and functionally appropriate by laboratory assistants. can be done up to date, quickly and accurately with the smartphone device of each employee or laboratory assistant and can directly monitor the state of the laboratory. Quality estimation in this study used the International Organization for Standardization (ISO) 9126 standard. The results showed that the developed information system for equipment inventory and monitoring of the CCTV computer laboratory complied with ISO 9126 standards on the aspects of usability, efficiency, functionality, and reliability.